Apolipoproteins do not add prognostic information beyond lipoprotein cholesterol measures among individuals with obesity and insulin resistance syndromes: the ARIC study. (29th August 2020) - Ndumele, Chiadi E; Matsushita, Kunihiro; Astor, Brad; Virani, Salim S; Mora, Samia; Williams, Emma K; Hoogeveen, Ron C; Blumenthal, Roger S; Sharrett, A Richey; Ballantyne, Christie M; Coresh, Josef
Abstract: Aims: There are conflicting guidelines regarding the measurement of apolipoproteins (apoB, apoA-1), in addition to standard lipoprotein cholesterol measures, for cardiovascular risk assessment among individuals with obesity or insulin resistance syndromes. This study aims to assess whether apolipoprotein assessments add prognostic information regarding coronary heart disease (CHD) risk beyond standard lipoprotein cholesterol measurements among individuals with obesity, diabetes, and the metabolic syndrome. Methods and results: We followed 9026 participants in the Atherosclerosis Risk in Communities (ARIC) study without cardiovascular disease at baseline (visit 4, 1996–99). We compared the associations of apoB, apoA-1, and their respective lipoprotein cholesterol measures with incident CHD events among individuals with and without obesity, the metabolic syndrome, or diabetes. Over a median follow up of 10.1 years, there were 903 CHD events. Among participants with obesity, the top quintiles of apoB (HR 2.00, 95% CI 1.40–2.85 compared with the bottom quintile) and the apoB/apoA-1 ratio (HR 2.47, 95% CI 1.53–4.01) did not demonstrate stronger associations with CHD than the top quintiles of non-high-density-lipoprotein cholesterol (non-HDL-C) (HR 2.54, 95% CI 1.65–3.89) and the ratio of non-HDL-C/HDL-C (HR 4.28, 95% CI 2.29–8.03). Analogous findings were seen among patients with diabetes and the metabolic syndrome. In models adjusted for non-HDL-C and HDL-C, apoB ( p  = 0.94) and apoA-1 ( p  = 0.55) were not significantly associated with CHD events among those with obesity, in contrast to non-HDL-C and HDL-C ( p  = 0.02 for both). Conclusions: Among individuals with obesity and insulin resistance syndromes, apolipoproteins did not provide prognostic information regarding CHD risk beyond that provided by non-HDL-C and HDL-C.